Evaluation of mechanical properties and physical interactions of a ternary blend of poly(ethylene‐co‐octene)/poly(ethylene‐co‐vinyl acetate)/poly(vinyl chloride) in the molten state. Issue 3 (26th November 2012) - Francisquetti, Edson L.; Pistor, Vinicios; Fiorio, Rudinei; Andrade, Mara Z.; Zattera, Ademir J.; Jacobi, Marly A. M.
Abstract In this work, ethylene‐co‐vinyl acetate (EVA), poly(ethylene‐co‐octene) (POE), and poly(vinyl chloride) (PVC) blends were processed in a molten state process using a corotating twin‐screw extruder to assess both the balance of mechanical properties and physical interactions in the melt state. Tensile measurements, scanning electron microscopy, and oscillatory rheometry were performed. By means of flow curves, the parameters of the power law as well as the distribution of relaxation times were assessed with the aid of a nonlinear regularization method. The mechanical properties for the EVA‐POE blend approximated the values for POE, while inclusion of PVC shifted the modulus values to those of neat EVA. The rise in modulus was corroborated by the PVC phase dispersion as solid particles that act as a reinforcement for the ternary blend. The rheological properties in the molten state show that the POE does not present molecular entanglement effects and so tends both to diminish the EVA mechanical properties and increase the fluidity of the blend. However, the addition of PVC both restored the EVA typical pseudoplastic feature and promoted the increase in the viscosity and the mechanical properties of the ternary blend. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013